Sperm competition experiments reveal low prezygotic postmating isolation between parasitic and nonparasitic lamprey ecotypes. Issue 4 (2nd April 2023) - Decanter, Nolwenn; Normand, Romane; Souissi, Ahmed; Labbé, Catherine; Edeline, Eric; Evanno, Guillaume
Abstract: The role of postmating sexual selection as a potential reproductive barrier in speciation is not well understood. Here, we studied the effects of sperm competition and cryptic female choice as putative postmating barriers in two lamprey ecotypes with a partial reproductive isolation. The European river lamprey Lampetra fluviatilis is anadromous and parasitic of other fish species, whereas the brook lamprey Lampetra planeri is freshwater resident and nonparasitic. We measured sperm traits in both ecotypes and designed sperm competition experiments to test the occurrence of cryptic female choice. We also performed sperm competition experiments either at equal semen volume or equal sperm number to investigate the role of sperm velocity on fertilization success. We observed distinct sperm traits between ecotypes with a higher sperm concentration and a lower sperm velocity for L. planeri compared with L. fluviatilis . The outcomes of sperm competition reflected these differences in sperm traits, and there was no evidence for cryptic female choice irrespective of female ecotype. At equal semen volume, L. planeri males had a higher fertilization success than L. fluviatilis and vice versa at equal sperm number. Our results demonstrate that different sperm traits between ecotypes can influence the male reproductive success and thus gene flow between L. planeri and L. fluviatilis . However, postmating prezygotic barriers are absent and thus cannot explain the partial reproductive isolation between ecotypes. Abstract : This study analyzes the effects of sperm competition and cryptic female choice as putative postcopulatory barriers in two lamprey ecotypes with a partial reproductive isolation. We observed different sperm traits between ecotypes, which influenced the outcome of sperm competition experiments, but we found no evidence for cryptic female choice.